2018
DOI: 10.5380/rf.v49i1.55744
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Grapple Skidder in Different Ground Inclinations

Abstract: Land slope contributes to decrease the productivity in the forestry sector activities, including skidding operations. Thus, it is important to study it in order to improve the forest operations planning. Based on this hypothesis, this study aims to analyze the times of the operational cycle and the productivity of the skidder in slope terrain. The study was conducted in Pinus taeda plantations of a forest company located in the CentralWest region of the state of Paraná, Brazil, in three slope classes: flat to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The operational cycle of the grapple skidder is divided into machine elements, which are composed of displacement without load, displacement with load, loading of wood, and unloading of wood. For displacements, the driving speed and engine power are higher-whereas for loading and unloading wood, they correspond to slow movements or movements only made by the machine's grapple [45].…”
Section: Discussionmentioning
confidence: 99%
“…The operational cycle of the grapple skidder is divided into machine elements, which are composed of displacement without load, displacement with load, loading of wood, and unloading of wood. For displacements, the driving speed and engine power are higher-whereas for loading and unloading wood, they correspond to slow movements or movements only made by the machine's grapple [45].…”
Section: Discussionmentioning
confidence: 99%
“…The slope was then reclassified in 10-percent interval break classes (Table 3). Our literature review found 0-20% presenting optimal conditions for wheeled equipment, such as harvesters, grapple skidders and tractors [9][10][11]30], and slopes of 30-40% resulting in severe productivity costs and machine dysfunction [6,10,12,30,31]. Our model used 10-percent breaks to denote decreasing machine operability, as 10 percent was the upper limit of the most optimal slope conditions found for harvesting equipment [41] and was used in other GIS terrain analyses [9].…”
Section: Slope Hoi Criterion Methodologymentioning
confidence: 99%
“…These two shapefiles were then converted into two raster layers on a 1-10 scale. Paved roads, (including all highways, rural roads and residential paved streets) received the lowest cost (1), unpaved roads (i.e., access roads) the median cost (5), and roadless areas the highest cost (10). These raster layers were then combined using a raster calculator to create the final 1-10 cost raster.…”
Section: Cost Distance To Highways Hoi Criterion Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, this factor had no significant effect on T cycle and P PMH , which possibly occurred because the maximum inclination observed in this study was only 9 degrees and, therefore, did not impose any major restrictions on equipment mobility. In clearcutting of a Pinus plantation with a lower mean individual tree volume, Diniz et al (2018b) reported that the wheeler skidder performance only tended to be negatively affected when the slope was above 26 degrees. On lesser slopes, the operator was able to compensate for increased cycle times on steeper areas by working more quickly on the flatter areas, thus avoiding any productivity reduction.…”
Section: Factors Affecting Performance and Modelling Of Productivitymentioning
confidence: 99%